Budowa i struktura naturalnego drzewostanu bukowego w rezerwacie „Zamkowa Góra” koło Kartuz - Karczmarski, Jan; Kunz, Łukasz (Leśne Prace Badawcze, 2010)
Four circular plots of area 0.25 ha were selected and investigated during the summer of 2006, to obtain data on DBH, height, crown size and trunk diameter as well as different classifications of all living trees. Additionally, an inventory of standing dead and fallen trees, evaluation of abundance and species composition of regeneration were performed and all data were collated in a plan showing all measured and recorded elements. The beech stand in the reserve was characterized by high stocking (597-692 m 3 /ha), large size of biggest trees (DBH up to 95 cm and height up to 43 m), as well as distinct spatial variability of developmental stages and phases associated with the different stand structures and composition (from single canopy layer to mixed, natural-like structure). Trees at distinct developmental stages co-occurred in homogeneous patches of size no smaller than 0.5 -1 ha. Typically there was only a small amount of dead biomass in the investigated stand, since most dead trees have already been removed from the reserve.